Strategies of Yota (Scartel) - 4G Operator in Russian Federation - Singh, Netra Pal; Kaushik, Manisha (Industrija, 2013)
Russian Federation is one of the high growth markets for telecom services which are expected to reach $48.5 billion by 2013.  With the granting of 4G LTE licenses, it is expected that 4G market in Russian Federation will be dominated by four cellular operators, i.e., MTS, Beeline, and MegaFon, Rostelecom along with two new startups, i.e., Osnova Telecom and Red Telecom (Iladi (2010)). In addition, other companies such as Yota, Synterra, COMSTAR, Freshtel etc. are also operating in Russian WiMax & LTE telecom market to provide similar services. This paper is an attempt to analyze some of the parameters of LTE turn Yota WiMax Telecom Operator in Russian Federation. The paper covers current achievements of Yota, its reach in Russian Federation, its network size & technology, its services, expansion plans for future, strategies for survival (in question) in a highly competitive market of big companies, and its ultimate fate.